EXPLORING ROLES OF PARENTAL INVOLVEMENT REGARDING SCHOOL-BASED VIOLENCE PREVENTION STRATGIES IN PRIMARY SCHOOLS - Saltiel Khololo Collen Mataboge (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This conceptualized paper sought to investigate the significance of parental involvement in school-based violence prevention strategies within the context of primary schools. The main research question guiding this study is: “What role does parental involvement play in shaping and enhancing school-based violence prevention strategies in primary schools?” This paper utilizes a qualitative approach which draws extensively from the review of scholarly books and articles (2018-2024) within the myriad of fields as data collection techniques. The interpretive paradigm is employed to analyse the collected data, allowing for a deeper insight of the complex dynamics between parental involvement and school-based violence prevention strategies. The findings of this study highlight the pivotal role of parental involvement in fostering safe and supportive school environments. The significance of this study lies in its potential to inform policymakers, the leadership and administrators about good practices which advocates for greater collaboration between schools and parents in mitigating issues of violence prevention.